Review on Feasibility of Gravity Power Generation Mechanism in Malaysia’s Sustainable Energy Program - Nabipour, Hadi; Prashanth PVS, Hari; Sundram, Hegaindran; Siing Kieh, Tiong; Mehranzamir, Kamyar; Wooi, Chin-Leong (International Journal of Integrated Engineering, 2020)
Malaysia being an oil-producing country has a vast amount of other natural resources that has not been used efficiently. In regard to focusing more in producing oil and gas, natural resources such as sunlight, water, wind, geothermal and gravity have not received a huge recognition by the government. Although hydroelectric power has been up and coming in the energy policies to promote power production in a sustainable way, other means of gravity power generation mechanism were not reviewed for this country, due to the lack of knowledge in this particular field. Gravity power generation mechanism can be of small scale which can actually fit in properly in areas that are off-the-grid. Hence, literature must be reviewed to discover the different type of gravity power generation mechanisms and run viability studies to implement the right system that offers sustainable energy production in rural parts of Malaysia. This review paper will analyze the feasibility of two systems in Malaysia, by assessing the viability of these system through the Malaysian economic, social, environmental, and sustainable standards.